Changes in Histological Structures of Soleus Muscle of the Male Rat in Response to Nandrolone Decanoate and Exercise - Jamshed Khan, Naseema Ahmad Jan, Muhammad Hanif, Ajmal Khan Bazai, Shazia Ramzan, Usmanullah (Pakistan Journal of Medical & Health Sciences, 2022)
Objective: Present study was conducted to investigate the histological changes produced by ND alone and in combination with exercise on soleus muscle. Study Design: Randomized controlled trial Place and Duration: Conducted at Animal House of Postgraduate Medical Institute (PGMI), Lahore during the year 2010 (From 20th Jan, 2010 to 13th April, 2010) for 12 weeks Methodology: Forty male rats were divided equally by randomized control trial (RCT)i.eAI (control), AII (ND5mg/kg intramuscular twice weekly) AIII (Exercise/swimming) AIV (ND & Exercise) for 12 weeks at the animal house of PGMI, Lahore during the year 2010. Data was recorded on various microscopic parameters viz; internalization of nuclei, splitting in muscle fibers, rounded or angular muscle fibers and diameter of fibers for control and experimental groups. Results: We found significant (P≤0.025, 0.037) differences among the groups receiving ND in comparison to control and exercise. Highly significant (P≤0.001) differences were observed in animals subjected to ND and exercise in comparison to control regarding internalization of nuclei. Muscle fiber splitting was observed in group AIII and AIV (P≤0.005) in comparison with control. Significant increase in diameter of muscle fiber was observed in group AIII (P≤0.013) and AIV (P≤0.001) in comparison to control. Similarly, minimum degenerative changes were observed showing angular or rounded fibers in group AIII and AIV in comparison to control. Conclusion: The instant results suggest that significant hypertrophy was observed in animals subjected to ND and exercise. Keywords: Soleus, splitting, diameter, internalization of nuclei